2022
DOI: 10.3233/jad-215484
|View full text |Cite
|
Sign up to set email alerts
|

Better Subjective Sleep Quality Partly Explains the Association Between Self-Reported Physical Activity and Better Cognitive Function

Abstract: Background: Physical activity has been associated with better cognitive function and better sleep quality. Yet, whether the beneficial effect of physical activity on cognitive function can be explained by an indirect pathway involving better sleep quality is unclear. Objective: To investigate whether sleep quality mediates the association between physical activity and cognitive function in adults 50 years of age or older. Methods: 86,541 community-dwelling European adults were included in the study. Physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 117 publications
0
4
1
Order By: Relevance
“…In contrast to previous research ( Wilckens et al, 2018 ; Cheval et al, 2022 ), we observed very little change in sleep and cognition from our exercise intervention, indicating there was not a mediating (indirect) effect. These results may be due to the lack of effect of exercise on sleep (“a” pathway, Figure 2 ), as we did observe associations between sleep and cognition (“b” pathway, Figure 2 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous research ( Wilckens et al, 2018 ; Cheval et al, 2022 ), we observed very little change in sleep and cognition from our exercise intervention, indicating there was not a mediating (indirect) effect. These results may be due to the lack of effect of exercise on sleep (“a” pathway, Figure 2 ), as we did observe associations between sleep and cognition (“b” pathway, Figure 2 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Results from cross-sectional studies indicate self-reported and objectively measured sleep may partially explain the association between physical activity and cognition ( Wilckens et al, 2018 ; Cheval et al, 2022 ). However, another observational study showed no mediating effect of self-reported sleep quality on the association between self-reported physical activity and global cognition ( Yuan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Better sleep quality has been a mediator for the effects of physical activity on cognitive function [30]. In this sample from the European Longitudinal Study on Aging (N =86,541), better subjective sleep quality partially explained the association between self-reported physical activity and cognitive function.…”
Section: Cognitive Effectsmentioning
confidence: 85%
“…Similarly, the question included the notion of "recent change in pattern", which might have confused participants who experienced poor sleep quality for several years. Thus, the current findings need to be confirmed using more complete measures of sleep quality and/or using devices-based measures of sleep parameters (Cheval et al, 2022). Fourth, we relied on a self-reported measure of physical activity based on two items.…”
Section: Strengths and Weaknessesmentioning
confidence: 89%